Awareness Campaign on the Risks of Excessive Smartphone Use Among Adolescents at SMPN 2 Tarogong Kidul, Jayaraga Village, Tarogong Kidul Subdistrict, Garut Regency - Gusgus Ghraha Ramdhanie Gusgus Ghraha Ramdhanie; Bambang Aditya Nugraha Bambang Aditya Nugraha; Sulastini Sulastini (Jurnal Pengabdian Masyarakat DEDIKASI, 2026)
Adolescence is a transitional period from childhood to adulthood characterized by severalsignificant changes in terms of physical, psychological, and social aspects. Adolescence isa period of exploration; they will try many new things. This condition encouragesadolescents to engage in risky behavior and unhealthy lifestyles. One of the risksassociated with this condition is the excessive use of electronic devices or gadgets. Weconducted socialization activities using health promotion and education methods at SMPN2 Tarogong Kidul, located in Jayaraga Village, Tarogong Kidul District, Garut Regency. Thefirst stage of the activity involves identifying the behavior patterns of students at theschool, based on the school's interpretation and perspective. The implementation stageinvolves the socialization of students at SMPN 2 Tarogong Kidul Garut, utilizing a deliverymethod that includes lectures, discussions, and questions and answers. During the finalstage, we assessed students' understanding through pretests and posttests, whichsupported the evaluation of their success. Based on the pre-test and post-test completedby the socialization participants, it is evident that the provided material has impartedknowledge to them, demonstrating that students are paying attention to the presentedcontent.